Pengaruh Pengetahuan Kewirausahaan Dan Motivasi Terhadap Minat Menjadi Pengusaha Dimasa Pandemi Covid-19 Di Surabaya - Dwi Widi Hariyanto (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
This review plans to decide the impact of Business venture Information and Innovative Inspiration on Business Interest locally in the city of Surabaya. This sort of examination is affiliated. Essential information were gathered through surveys distributed to respondents. The population in this review isn't restricted by unique models. The example in this review added up to 94 respondents. The consequences of this review show that at the same time, the impact of Business Information and Pioneering Inspiration on Business Interests in networks in the Surabaya matured 25-35 years. To some extent the impact of Enterprising Information and Business venture Inspiration has a positive and critical impact on Business Interest. According to the aftereffects of the coefficient of assurance, the R Square worth of 0.373 or 37.3% of the Pioneering Interest variable can be clarified by the Enterprising Information and Innovative Inspiration variable and the leftover 62.7% is clarified by different factors not inspected in this review.